A facile method for in situ fabrication of silica/cellulose aerogels and their application in CO2 capture. (15th May 2020) - Miao, Yingju; Pudukudy, Manoj; Zhi, Yunfei; Miao, Yingchun; Shan, Shaoyun; Jia, Qingming; Ni, Yonghao
Graphical abstract: Highlights: Synthesis of composite aerogels by simultaneous addition of cellulose and silica. Skeleton structure of composite aerogels changed with silica:cellulose ratios. CO2 uptake of composite aerogels decreased with increasing Si content. CO2 /N2 selectivity of composite aerogels increased with increasing Si content. Abstract: Old corrugated containers-based cellulose and fly ash-based fresh wet silica gel were used as raw materials for in situ synthesis of a series of silica/cellulose aerogels in NaOH/urea solution. At a silicon to cellulose ratio of less than 2.5:1, the skeleton structure of the synthesized composite material was dominated by fibrils decorated with spherical silica nanoparticles. At a silicon to cellulose ratio of higher than 2.5:1, the skeleton structure of the composite material was dominated by spherical silica particles interspersed with cellulose. The synthesized composite material was applied to capture CO2 at ambient temperature and pressure. We observed that with increasing silicon content, the CO2 adsorption capacity of the composite material decreased (regardless of its dominant structure), while its selectivity for CO2 /N2 increased. This work presents a facile method for the synthesis of adsorption material that has high capacity and selectivity for CO2 .